Does elite European match-play affect salivary immunoglobulin-A and cortisol in soccer players? The influence of playing status and match outcome - Morgans, R., Oliveira, R.; Rhodes, D.; Patrick, O.; Ceylan, H. I.; González-Fernández, F. T.; Linán-González, A.; Moreira, A. (Frontiers in Physiology, 2024)
Introduction: The aims of this study were to: a) investigate salivary immunoglobulin A (s-IgA) and cortisol (s-Cort) responses to nine competitive fixtures in starting and non- starting soccer players; and b) compare s-IgA and s-Cort responses of starters and non-starters considering match outcome.